Edukasi Fenomena Geologi Gua Warak dan Gua Macan Putih untuk Pengembangan Potensi Geowisata di Kota Metro - Ilham Dani; Bagus Sapto Mulyatno; Ordas Dewanto; I Gede Boy Darmawan (Unri Conference Series: Community Engagement, 2021)
The condition of the Covid-19 pandemic that has occurred since the beginning of 2020 has paralyzed tourism activities in Metro City, Lampung Province. One of the affected tourist objects is the Warak Cave and the Macan Putih Cave, which are located in Tejosari Village, East Metro District. The development of tourist attractions which began to squirm since 2018 was paralyzed due to the outbreak. Entering the new normal era, it can be used as a momentum to introduce the concept of geotourism in Tejosari Village so that the development of tourist objects becomes more attractive in attracting tourists. The method used in this service activity is by direct observation in the field regarding geological conditions which are then disseminated to the community around the cave and to the managers of tourist attractions. The effort made by the service team is to provide counseling about the concept of geotourism and the efforts that can be made to optimize the tourism potential around the cave. The results obtained from this activity are an increase in public knowledge about geological conditions and the concept of geotourism.